2010
DOI: 10.1517/14740338.2010.485190
|View full text |Cite
|
Sign up to set email alerts
|

Statin administration and risk of cholecystectomy: a population-based case-control study

Abstract: The results of our large population-based study suggest that the use of statins reduces the risk of surgery for gallstone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…classified patients as never users of lipid‐lowering drugs, and current users if their last prescription for statins was redeemed less than 90 days (3 months) before the index date. From the above point, for the lower statin users in the two studies, the statin use was less than 6 months (the threshold of when it may act).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…classified patients as never users of lipid‐lowering drugs, and current users if their last prescription for statins was redeemed less than 90 days (3 months) before the index date. From the above point, for the lower statin users in the two studies, the statin use was less than 6 months (the threshold of when it may act).…”
Section: Discussionmentioning
confidence: 95%
“…Merzon et al . 's study defined patients who filled prescriptions for fluvastatin, lovastatin, pravastatin, simvastatin, atorvastatin or rosuvastatin in the 180 days (6 months) prior to their index date were considered to have been “exposed” to a statin treatment. Erichsen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Merzon et al conducted a population-based case--control study in Israel using the database from Clalit Health Services. The results suggest that the use of statins reduces the risk of surgery for gallstone disease (OR 0.73, 95% CI 0.62 to 0.87) [19]. Erichsen et al [20] conducted a population-based case--control study using a medical database from northern Denmark.…”
Section: Discussionmentioning
confidence: 99%
“…Few epidemiological studies have investigated the association between statin use and risk of gallstone disease, and results have been inconsistent. Four recent studies reported that statin use is associated with a significant reduction in the risk of gallstone disease [17][18][19][20]. By contrast, two studies reported no statistically significant association between statin use and gallstone risk [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 However, the limited evidence of the association of statin medications and gallstone disease in clinical studies is conflicting, with some studies suggesting reduced risk of gallstone disease in statin users, whereas other studies did not reproduce similar findings. [10][11][12][13][14] Therefore, there is a need for evidence evaluating the association between statin use and the occurrence of gallstone disease in an unselected population in general and in a US-based population in particular. 15,16 To address these limitations, we conducted a study using data from a large American military health care system (MHS) to evaluate the association between statin use and gallstone disease in a cohort of patients who were followed longitudinally for more than 8 years with similar access to care and complete follow-up.…”
Section: Introductionmentioning
confidence: 99%